Behavioural Finance: Understanding The Psychology Of Investors in Indian Equity Markets - Wadhwa, Megha (2009)
This thesis attempts to evaluate the Efficient Market Hypothesis and its limitations. It attempts to prove that Indian markets are not completely efficient, which provides rational investors with opportunities for abnormal profits. It identifies the behavioural biases that are present in the Indian markets. Two case studies were carried out, both proving that prices do not fully represent fundamentals. Seven depth interviews were conducted, which generated an in depth discussion on the volatilities of the Indian equity market and why are such volatilities present, on the Indian investor mindset, on how an individual investor may differ from a professional fund manager, on age and gender as variables that affect investment decisions and on what one must and must not do in order to be a successful investor. The expert views strongly suggest that equity is purely a long term phenomenon. After a thorough analysis of the case studies and interviews, this thesis adheres to the conclusion that Statman (1999) has generated in his paper “Behavioural Finance: Past Battles and Future Engagements”. The Efficient Market Hypothesis is sliced into two parts. One is that investors cannot systematically beat the market. the other is that security prices are rational. Behavioural finance has shown that prices are not always rational, thus it is wise to accept the Efficient Market Hypothesis in the “beat the market” sense, but reject it in the “rational prices” sense. Finally I suggest an alternative measure of calculating investor returns using Earnings Per Share. I would like to spell out the conclusion of this thesis in one line. “The market knows best, and if an investor knows that, he knows better.”